2021
DOI: 10.1007/s11356-021-16060-1
|View full text |Cite
|
Sign up to set email alerts
|

Pertinence of nutriments for a stalwart body

Abstract: Nutrition plays a significant role in the prevention and treatment of common diseases. Some superb dietary choices such as functional foods and nutriments can surely help fight against certain diseases and provide various advantages to an individual’s health. Plants have been regarded as a primary source of highly effective conventional drugs leading to the development of potential novel agents, which may boost the treatment. Growing demand for functional foods acts as an aid for the producers to expand in agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…However, the methanol extract of L. cernuum had an IC 50 of > 1,000 µg/mL, indicating that it does not have antioxidant activity. This finding is consistent with the qualitative phytochemical results, which showed that the tested L. cernuum methanol extract does not contain flavonoid or alkaloid compounds, which are both known to have antioxidant activity [90,91]. Based on the results, it can be concluded that the methanol extracts of M. malabathricum, T. micrantha, C. odorata, D. linearis and B. cernua have more effective antioxidant activities than those from virgin lands with lower doses or IC 50 .…”
Section: Antioxidant Activitysupporting
confidence: 88%
“…However, the methanol extract of L. cernuum had an IC 50 of > 1,000 µg/mL, indicating that it does not have antioxidant activity. This finding is consistent with the qualitative phytochemical results, which showed that the tested L. cernuum methanol extract does not contain flavonoid or alkaloid compounds, which are both known to have antioxidant activity [90,91]. Based on the results, it can be concluded that the methanol extracts of M. malabathricum, T. micrantha, C. odorata, D. linearis and B. cernua have more effective antioxidant activities than those from virgin lands with lower doses or IC 50 .…”
Section: Antioxidant Activitysupporting
confidence: 88%
“…Bioinformatics, and specifically drug docking is a new approach to the check the potential of different bioactive compounds to be used as potential drug targets. In order to screen the role of sesame bioactive compounds against CVD, Hemoglobin beta subunit protein (HBB) was used as target protein for sesame bioactive compounds [ [22] , [23] , [24] , [25] ].…”
Section: Introductionmentioning
confidence: 99%
“…Heart disease is linked to several cardiometabolic risk factors, including hypercholesterolemia, diabetes, high blood pressure, obesity, and a sedentary lifestyle. Triglycerides (TG), total cholesterol (CT), cholesterol of the low-density lipoprotein (LDL-C), and cholesterol of the high-density lipoprotein (HDL-C) all rise at higher rates in dyslipidemia, a metabolic disorder that is very common (Bakhtiyari et al, 2022;Kaur et al, 2021;Guilbert, 2003).…”
Section: Introductionmentioning
confidence: 99%